Faktor Penghambat Perlindungan Hak Privasi Nasabah Akibat Kebocoran Data Pribadi Pada Aplikasi Pinjaman Online Dalam Perspektif Hukum Perdata - Zulkarnain Saleh; Weny Almoravid Dungga; Sri Nanang Meiske Kamba (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2024)
The aim of this research is to discuss the protection of the privacy rights of customers who carry out electronic transactions on online loan applications in light of Law Number 27 of 2022 concerning personal data protection. By reviewing the problems regarding leaks of personal data in online loan applications as well as factors inhibiting legal protection of customers' personal data for actions that are detrimental to customers, this research can take advantage. The method used in this research is a normative legal research method and is supported by empirical data. The results of this research suggest that it is necessary to carry out regular and continuous supervision by the Government, in this case the Police, the Consumer Dispute Resolution Agency, and the Indonesian Consumers Foundation. For business actors in online loan applications, then carry out good coordination between related and authorized parties in resolving a case/case.